Semi-quantitative assessment of paraspinal muscle fat infiltration in single-level C5–6 cervical spondylosis using gray-level thresholding on conventional MRI: associations with disc degeneration and posture-related segmental angular change - Yifei Li; Liang Zhao; Wei Zhang; Xiubo Ge; Haitao Lu; Haoran Shi; Haiyang Yu (Frontiers in Medicine, 2026)
Background Cervical spondylosis at C5–6 is common, but conventional imaging may not fully capture paraspinal muscle composition or posture-related segmental angular behavior. This study assessed layer-specific paraspinal muscle fat infiltration (FI) and cross-sectional area (CSA) on conventional MRI and examined their associations with C5–6 disc degeneration and posture-related angular change (PAC). Methods In this retrospective cross-sectional study, 94 patients with single-level C5–6 cervical spondylosis who underwent cervical MRI and standing lateral radiography between January 2023 and December 2025 were included. At the C5–6 disc level, bilateral splenius capitis (SPL), semispinalis capitis (SCap), and combined multifidus plus semispinalis cervicis (MF + SCer) were manually segmented. FI was calculated as a semi-quantitative area percentage using a fixed 8-bit gray-level threshold (79–255), and CSA was measured on calibrated axial T2-weighted images. PAC was defined as the absolute difference between standing radiographic and supine MRI local C5–6 Cobb angles; patients were classified as low-PAC/relatively stiff (|PAC| ≤ 5°) or high-PAC/relatively mobile (|PAC| > 5°). Results FI in all three muscle groups increased with higher Pfirrmann grades, whereas CSA did not differ significantly across grades. Pfirrmann grade was independently associated with FI in the SPL, SCap, and MF + SCer after adjustment for age and sex. Compared with the high-PAC group, the low-PAC group showed higher FI in the SPL, SCap, and MF + SCer, and these differences remained significant after adjustment for age, sex, BMI, and Pfirrmann grade. CSA did not differ significantly between PAC phenotypes. Conclusions In patients with single-level C5–6 cervical spondylosis, paraspinal muscle alteration was characterized primarily by increased FI, whereas CSA reduction was not evident. Compared with CSA, semi-quantitative FI measured on conventional MRI may be more sensitive for detecting observable changes in muscle composition. Higher FI in the superficial and intermediate posterior extensor muscles was associated with a low-PAC/relatively stiff phenotype. Combining PAC with paraspinal muscle FI may provide supplementary imaging information on segmental angular differences between weight-bearing and non-weight-bearing positions; however, the clinical relevance of this combined assessment requires prospective validation using quantitative fat imaging and clinical or functional outcomes.